Next-generation sequencing reveals high concordance of recurrent somatic alterations between primary tumor and metastases from patients with non-small-cell lung cancer - Vignot, Stéphane; Frampton, Garrett M; Soria, Jean-Charles; Yelensky, Roman; Commo, Frédéric; Brambilla, Christian; Palmer, Gary; Moro-Sibilot, Denis; Ross, Jeffrey S; Cronin, Maureen T; André, Fabrice; Stephens, Philip J; et al. (Journal of clinical oncology, 2013)
Characterization of the genomic changes that drive an individual patient's disease is critical in management of many cancers. In patients with non-small-cell lung cancer (NSCLC), obtaining tumor samples of sufficient size for genomic profiling on recurrence is often challenging. We undertook this study to compare genomic alterations identified in archived primary tumors from patients with NSCLC with those identified in metachronous or synchronous metastases. Primary and matched metastatic tumor pairs from 15 patients were analyzed by using a targeted next-generation sequencing assay in a Clinical Laboratory Improvement Amendments laboratory. Genomic libraries were captured for 3,230 exons in 182 cancer-related genes plus 37 introns from 14 genes often rearranged in cancer and sequenced to high coverage. Among 30 tumors, 311 genomic alterations were identified of which 63 were known recurrent (32 in primary tumor, 31 in metastasis) and 248 were nonrecurrent (likely passenger). TP53 mutations were the most frequently observed recurrent alterations (12 patients). Tumors harbored two or more (maximum four) recurrent alterations in 10 patients. Comparative analysis of recurrent alterations between primary tumor and matched metastasis revealed a concordance rate of 94% compared with 63% for likely passenger alterations. This high concordance suggests that for the purposes of genomic profiling, use of archived primary tumor can identify the key recurrent somatic alterations present in matched NSCLC metastases and may provide much of the relevant genomic information required to guide treatment on recurrence.